Hydrogenic concentration of gold in alluvial placers of the Egorevskoe area (Salair) - Dutova E. M. Ekaterina Matveevna; Bukaty M. B.; Nevolko A. L.; Pokrovsky D. S.; Shvartsev S. L. Stepan Lvovich (2006, 2006)
Based on results of studying the geochemistry and gold distribution of groundwaters in the Egor'evskoe gold-bearing area, a mechanism of gold mobilization, migration, and accumulation in mountain-forest landscape is proposed. Gold mass transfer is part of an ore-generating process running in a water-rock system. Hydrogenic concentration of gold in placers is equally determined by physicochemical processes of secondary mineral formation and hydrodynamic conditions. The amounts of accumulated gold depend on the gold-producing capacity and volume of waters involved in the mineral formation and on the duration of this process.